Reliability of sagittal photographic spinal posture assessment in adolescents. - Perry M; Smith A; Straker L; Coleman J; O'Sullivan P (Advances in Physiotherapy, 2008)
Posture and adolescent spinal pain may be linked, so adolescent posture measurement is important. Static photographic analysis of posture is practical for large-scale studies of adolescents, but only one adolescent study has investigated its reliability. The aim was therefore to assess the reliability of photographic spinal posture assessment in adolescents. Inter-rater reliability was measured, as the purpose was to assess the method for large-scale epidemiological studies with multiple raters. Twenty-two healthy adolescent subjects (11 males, 11 females) aged 13-17 were photographed by four different examiners while standing, sitting and slumped. Eight spinal postural angles and four distance measures were derived. Inter-rater reliability was quantified by interclass correlation coefficients (ICCs) for consistency, ICCs for absolute agreement between raters and standard errors of measurement (SEMs). Inter-rater reliability was fair (ICC >0.4) to good (ICC >0.75) for all measures in standing except pelvic tilt and sway angle, and for all measures in sitting except head flexion and craniocervical angle. Poorer ICCs for agreement than consistency were observed, reflecting a significant rater effect for most measures. Photographic analysis of adolescent posture has fair reliability, and is appropriate for large-scale adolescent studies. Future studies should observe several precautions to optimize reliability.